354 Trends in the Drug-Sparing Effects for Benzodiazepines and Prescription Opioids among Insomnia Patients on Suvorexant in the US. (3rd May 2021) - Kale, Hrishikesh; Khandker, Rezaul; Shah, Ruchit; Botteman, Marc; Meng, Weilin; Jootun, Murvin; Qureshi, Zaina
Abstract: Introduction: Use of benzodiazepines to treat insomnia has been associated with serious side effects and abuse potential. Insomnia patients are at high risk of opioid abuse and better sleep patterns may help to reduce opioid use. This study examined the trend in the use of benzodiazepines and prescription opioids before and after initiation of suvorexant in insomnia patients. Methods: The study analyzed 2015–2019, Optum Clinformatics Data Mart. Insomnia patients, identified using ICD-9/10 codes and prescribed suvorexant were included. The study included incident (newly diagnosed) and prevalent cohorts of insomnia patients. The proportion of patients on benzodiazepines or prescription opioids were calculated for 12 monthly intervals before (pre-period) and after initiation of suvorexant (post-period). Interrupted time series (ITS) analysis was conducted to assess trends for use of benzodiazepine or prescription opioids over time. Results: A total of 5, 939 patients from the incident insomnia cohort and 18, 920 from the prevalent cohort were included. For the incident cohort, mean age was 64.47 (SD: 15.48), 63% were females, 71% had Medicare Advantage coverage, 59% had Charlson comorbidity index score (CCI) ≥ 1, 27% had an anxiety disorder and 16% had substance abuse disorder. Prevalent insomnia cohort was similar but had higher CCI. Results from ITS suggested that at the beginning of the pre-period, 28% of incident insomnia patients used either opioids or benzodiazepines with the rate of use in the pre-period increasing by 0.11% per month. In the post-period, the rate of use decreased by 0.33% per month. About 26% patients used benzodiazepines or opioids at 12-month after suvorexant initiation. In the absence of suvorexant, this proportion would have been 31%. Similar findings were observed for the prevalent insomnia cohort. A larger decrease was observed for opioid use than benzodiazepines. Conclusion: The rate of benzodiazepines or prescription opioid use decreased over time after the initiation of suvorexant. Suvorexant has the potential to reduce the use of opioids and benzodiazepines among insomnia patients. Further research is needed to confirm these findings. Support (if any): This study was sponsored by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA.